IRRITABLE BOWEL SYNDROME IN CHILDREN: DIAGNOSTICS AND MODERN APPROACHES TO THERAPY - S.Yu. Tereshchenko (Педиатрическая фармакология, 2006)
In the article modern data on prevalence, diagnostic criteria and approaches to the treatment of irritable bowel in children are presented. The issues of the terminology and classification of recurrent abdominal pains in children are clarified, the basic pathophysiological mechanisms of the disease are indicated. Particular emphasis has been placed on the efficient therapy of the different clinical variants of irritable bowel syndrome. The role of modern spasmolytic drugs in the treatment of abdominal pain syndrome and the rational usage of laxatives in constipation in children is shown.Key words: children, irritable bowel syndrome, diagnostics, treatment.